The Dynamics of Transitional Justice : International Models and Local Realities in East Timor. - Kent, Lia (Taylor and Francis, 2012)
The Dynamics of Transitional Justice draws on the case of East Timor in order to reassess how transitional justice mechanisms actually play out at the local level. Transitional justice mechanisms - including trials and truth commissions - have become firmly entrenched as part of the United Nations 'tool-kit' for successful post-conflict recovery. It is now commonly assumed that by establishing individual accountability for human rights violations, and initiating truth-seeking and reconciliation programs, individuals and societies will be assisted to 'come to terms' with the violent.